Proceedings of the Eleventh ACM on Hypertext and Hypermedia 2000
DOI: 10.1145/336296.336361
|View full text |Cite
|
Sign up to set email alerts
|

Ontology-supported and ontology-driven conceptual navigation on the World Wide Web

Abstract: This paper presents the principles of ontology-supported and ontology-driven conceptual navigation. Conceptual navigation realizes the independence between resources and links to facilitate interoperability and reusability. An engine builds dynamic links, assembles resources under an argumentative scheme and allows optimization with a possible constraint, such as the user's available time. Among several strategies, two are discussed in detail with examples of applications. On the one hand, conceptual specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…The upgradeable provisions for the business operators can reduce the contrast between individual farming practice and the relevant technological actions. Earlier researches, such as in bioinformatics (Baker et al, 1999;Lambrix and Edberg, 2003), in World Wide Web design (Crampes and Ranwez, 2000;Liddle et al, 2003;Sunagawa et al, 2003) and medical informatics (Achour et al, 2001;Gennari et al, 2002;Musen, 1998) justified ontology development as an established and workable concept in effective knowledge modelling. Unlike other domains, we used the ontology development approach as a progressive way to model knowledge from the dairy operational domain, which was utilised for developing and delivering specific and targetrelevant DSS because of its generic capability.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The upgradeable provisions for the business operators can reduce the contrast between individual farming practice and the relevant technological actions. Earlier researches, such as in bioinformatics (Baker et al, 1999;Lambrix and Edberg, 2003), in World Wide Web design (Crampes and Ranwez, 2000;Liddle et al, 2003;Sunagawa et al, 2003) and medical informatics (Achour et al, 2001;Gennari et al, 2002;Musen, 1998) justified ontology development as an established and workable concept in effective knowledge modelling. Unlike other domains, we used the ontology development approach as a progressive way to model knowledge from the dairy operational domain, which was utilised for developing and delivering specific and targetrelevant DSS because of its generic capability.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Finally, conceptual navigation [9] and conceptual hypermedia [6] discuss the use of taxonomies or ontologies to support browsing of the annotated information space. Vox Populi differs from their approach because a thesaurus is used not only to annotate (or classify [6]) information items but also to establish semantic relations between them.…”
Section: Related Workmentioning
confidence: 99%
“…The idea is to replace direct linking between fragments (often called horizontal linking) by inferred links that correspond to paths starting from a fragment, traversing one or several ontology concepts, and ending on another fragment [1] [2]. We have observed that these inferences provide semantically relevant links because users (authors) are generally able to establish correctly typed links from their fragments to the relevant concepts.…”
Section: Link Inferencementioning
confidence: 99%